Existential transformations in the process of facing amyotrophic lateral sclerosis by the family caregiver - Lays Pedrosa dos Santos Costa; Isabel Comassetto; Regina Maria dos Santos; Amuzza Aylla Pereira dos Santos; Guilherme Oliveira de Albuquerque Malta; Karine de Melo Cezar Alves (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To understand the existential transformations of the family caregiver of a person living with Amyotrophic Lateral Sclerosis. Method Qualitative study based on assumptions of Martin Heidegger Existential Phenomenology, with 12 family caregivers of the person with Amyotrophic Lateral Sclerosis, in Alagoas. The testimonies were obtained from June 2019 to March 2020 and analyzed, categorized, and discussed based on the theoretical-philosophical framework adopted and thematic literature. Results Phenomenological sense of the existential transformations of the family caregiver of a person living with Amyotrophic Lateral Sclerosis, unveiled with the categories: Being the caregiver of the person living with ALS; Being responsible for decision making; Resignifying the existence in view of the possibility of loss; Spirituality influencing the transformation process. Conclusions The family caregiver has an appropriate life due to the inherent vicissitudes of the disease, which provides moving moments that lead him to rethink his existence and to value life.